Polypseudorotaxane hydrogel based on Tween 80 and α-cyclodextrin for sustained delivery of low molecular weight heparin. (1st December 2022) - Tang, Bo; Yang, Xuewen; Zhang, Aiwen; Wang, Qiuxiang; Fan, Lei; Fang, Guihua
Abstract: Low molecular weight heparin (LMWH), an anionic polysaccharide, has been widely used as a clinical anticoagulant. However, repeated subcutaneous injection is sometimes required due to its short half-life. To reduce the dosing frequency, the injectable polypseudorotaxane hydrogel was fabricated by inclusion complexation formation between Tween 80 and α-Cyclodextrin (αCD) for sustained release of LMWH. The physicochemical properties of such hydrogel were characterized by SEM, XRD, DSC, and FTIR. This hydrogel showed shear-thinning and thixotropic behavior and was easily injected through standard syringe needles. The gelation time, mechanical strength, shear viscosity, in vitro drug release rate, in vitro hydrogel dissolution rate, and in vivo hydrogel retention could be tuned by αCD concentration in the hydrogel. In vivo safety evaluation indicated that the polypseudorotaxane hydrogel was biocompatible. Most importantly, this polypseudorotaxane hydrogel could sustain release of LMWH after subcutaneous injection. Graphical abstract: Unlabelled Image